A Speed Optimization Strategy for Smooth Merging of Connected and Automated Vehicles at T-Shape Roundabout - Khurrum Jalil; Yuanqing Xia; Muhammad Noaman Zahid; Tayyab Manzoor (IEEE Access, 2022)
This paper establishes a novel holistic T-shape roundabout coordination system (TCS) that addresses the connected and automated vehicles (CAVs) flow at a typically isolated T-shape roundabout. The TCS optimizes the states of each approaching vehicle to the roundabout in a receding horizon control framework that aims to minimize the total delay time, and ensures the smooth crossing. The optimized states are broadcasted immediately by TCS, enabling the CAVs to form a cluster and tune their speed to transit the roundabout with negligible stop-delay. We evaluate the effectiveness of the proposed TCS method under the various traffic flow demand. From the executed simulation, it is observed that the optimization process usually improves the vehicle’s average speed and reduces both the traffic density and idling. As a consequence, the fuel consumption of each vehicle around the roundabout is also reduced. Finally, these outputs are compared with the traditional method, showing that the roundabout performance significantly improves in the case of the proposed scheme, and vehicles have rapid optimization for a smooth crossing.